Multigrade Teaching Environment: Unleashing the Impact on Students’ Literacy Outcomes in Under Resource Areas - Ruth Salamet,; Majeed, Alia (IJLTP, 2025)
Multigrade teaching in Pakistan is important because it tackles the nation’s particular literacy needs particularly in underprivileged areas. Multigrade teaching has emerged as a viable way to educate all pupils considering teacher shortages, packed classrooms, and inadequate school facilities, especially in rural and low-income metropolitan regions. Comprehending multigrade teaching in Pakistan provides valuable perspectives on how to modify education to surmount these obstacles and attain inclusive, high-quality education for everyone. Present research was done to study the impact of multigrade teaching on the students’ literacy outcomes in rural areas. The objectives of this research were to a) assess the impact of multigrade teaching in improving students’ literacy outcomes; and ) identify the challenges faced by teachers in implementing multigrade teaching. This study was delimited to the all the multigrade teachers of urban and rural areas of Islamabad, Rawalpindi and AJK. A questionnaire was prepared for Head teachers and teachers. Questionnaire was used as an instrument of research study for collection of data. The convenient sampling method was applied for input data of study by selecting 40 teachers randomly. Data was collected from Head teachers and teachers. The validity and reliability of the instrument was checked by the experts through percentage data was analyzed. Each statement was analyzed separately by SPSS. The findings of the study showed that majority of the public-school teachers agreed that multigrade teaching enhances students’ literacy skills. Majority of the teachers agree that good planning , effect teaching strategies and activities improve teaching learning process in multigrade teaching in rural areas to improve the learners’ outcomes. However, time management, provision of quality educational facilities, technology-embedded learning environment and are big challenges in improving multigrade teaching.